2012
DOI: 10.1111/scs.12009
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' perceptions of working according to standardized care plans: a questionnaire study

Abstract: The nurses had overall positive perceptions of working according to an SCP mainly in terms of usability, documentation and quality of care. The implementation process was not optimal and it was doubtful whether the SCP rendered any positive side effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Questionnaires were distributed to all staff when the pathway had been implemented for approximately 1 year. The composition of the questionnaire was based on a previously used questionnaire [ 28 ] with additional questions inspired by previous studies [ 15 , 23 , 29 ], and it encompassed the following: the general impression of the pathway, utilization, patient/family involvement, usability, documentation, care quality, and the implementation process. Additional file 2 provides the questions included in the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Questionnaires were distributed to all staff when the pathway had been implemented for approximately 1 year. The composition of the questionnaire was based on a previously used questionnaire [ 28 ] with additional questions inspired by previous studies [ 15 , 23 , 29 ], and it encompassed the following: the general impression of the pathway, utilization, patient/family involvement, usability, documentation, care quality, and the implementation process. Additional file 2 provides the questions included in the questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Dunn, 2012) and affirm that in decision-making, they prioritise their experience on the content of the plans (Jakobsson & Wann-Hansson, 2013;Svensson et al, 2012). Finally, lack of interest could influence negatively the individualisation process (Baraki et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, nurses acknowledge that they do not use the CP as an instrument of communication between them. Because they do not comment on their content, especially if there are discrepancies (Estrada & Dunn, ) and affirm that in decision‐making, they prioritise their experience on the content of the plans (Jakobsson & Wann‐Hansson, ; Svensson et al, ). Finally, lack of interest could influence negatively the individualisation process (Baraki et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…, Bjurling‐Sjöberg et al . , Jakobsson & Wann‐Hansson ). SCPs may also help staff improve patient outcomes, reduce length of hospital stays, and enhance teamwork and record keeping (Rycroft‐Malone et al .…”
Section: Introductionmentioning
confidence: 97%
“…Studies have shown that hospital staff believe SCPs increase their ability to provide high-quality patient care (Lee 2005, 2006, Dahm & Wadensten 2008, P€ oder et al 2011, Svensson et al 2012, Bjurling-Sj€ oberg et al 2013, Jakobsson & Wann-Hansson 2013. SCPs may also help staff improve patient outcomes, reduce length of hospital stays, and enhance teamwork and record keeping (Rycroft-Malone et al 2004, Deneckere et al 2013, Deng et al 2014.…”
Section: Introductionmentioning
confidence: 99%